1992
DOI: 10.3758/bf03213382
|View full text |Cite
|
Sign up to set email alerts
|

Landmark use by pigeons in a touch-screen spatial search task

Abstract: Pigeons obtained food by pecking at an unmarked target location on a video screen equipped with a touch-sensitive frame. The target area was located near the top edge of the screen in Experiment 1 and near the left edge of the screen in Experiment 2. On baseline trials, a graphic landmark was located below and left of the target (Experiment 1) or below and right of the target (Experiment 2). In both experiments, baseline search distributions showed a single peak and were roughly symmetrical about the target ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 20 publications
7
72
1
Order By: Relevance
“…This difference likely 334 reflects the physical properties of the two cues, with the large, blue cue providing edge or 335 boundary information and the small, red cue serving as a discrete landmark. The pattern of 336 results is consistent with previous studies that have found differences in control by edges and 337 discrete landmarks in birds, with distance from an edge being more important than distance 338 along that edge (Cheng & Sherry, 1992;Spetch, Cheng, & Mondloch, 1992).…”
Section: Single-cue Tests 326supporting
confidence: 85%
“…This difference likely 334 reflects the physical properties of the two cues, with the large, blue cue providing edge or 335 boundary information and the small, red cue serving as a discrete landmark. The pattern of 336 results is consistent with previous studies that have found differences in control by edges and 337 discrete landmarks in birds, with distance from an edge being more important than distance 338 along that edge (Cheng & Sherry, 1992;Spetch, Cheng, & Mondloch, 1992).…”
Section: Single-cue Tests 326supporting
confidence: 85%
“…Pigeons can learn to search for an unmarked goal location on a computer monitor, with graphic objects as landmarks and responses recorded by a touch-sensitive frame (touch screen; e.g., Spetch, Cheng, & Mondloch, 1992; for a review, see Cheng, Spetch, Kelly, & Bingman, 2006). In a touch-screen study on both pigeons and humans, Spetch (1995) demonstrated overshadowing in landmark use.…”
Section: Landmarks 1: Cue Competitionmentioning
confidence: 99%
“…Trials of the same type were combined across test sessions. These data were then used to compute the peak place of searching in the horizontal and vertical dimensions, using the iterated median procedure as described in Cheng (1989) and Spetch et al (1992). This procedure determines the middle ofthe highest region in the distribution.…”
Section: Data Recording and Analysismentioning
confidence: 99%
“…Two types of evidence indicate that a subject uses a particular landmark: (I) the subject shifts its search location in response to landmark shifts, and (2) accurate search is disrupted by the absence of the landmark. In a series of experiments using a laboratory task in which food is hidden on the floor of a spatial arena, Cheng and his colleagues (e.g., Cheng, 1988Cheng, , 1989Cheng, , 1994Cheng & Sherry, 1992) have clearly demonstrated that pigeons use visual landmarks to locate a hidden goal, and they have identified several principles of pigeons' landmark-based search.Pigeons' landmark-based search has also been investigated in a touch-screen task in which pigeons search for an unmarked goal on the surface of a monitor (Spetch, Cheng, & Mondloch, 1992;Spetch & Mondloch, 1993;Spetch & Wilkie, 1994 …”
mentioning
confidence: 99%
See 1 more Smart Citation